REPRODUCTIVE STATUS OF MUDSKIPPERS (FAMILY GOBIIDAE) IN THE KARANGTALUN MANGROVE FOREST, CILACAP - Aura Rose Sahara; Dewi Wisudyanti Budi Hastuti; Riviani Riviani; Anandita Ekasanti; Dewi Nugrayani (Universitas Mataram, 2025)
Mudskipper is a typical and unique fish in mangrove areas that is important for balancing mangrove ecosystems (keystone species) so it is necessary to have the availability of this fish in nature, namely by the process of reproduction. The purpose of this study was to determine the reproductive characteristics (TKG, IGS, sex ratio, and fecundity) and analyze the histology of the gonads of spadefish found in the Karangtalun Mangrove Forest Area. This research method includes purposive sampling method to determine research stations based on location characteristics. The mudskipper obtained were measured for length, weight, sex identification, dissection, gonad weighing and egg count, and Hemactoxylin-Eosin staining (Histology). The number of skinks found at both stations was 119 with a sex ratio of males and females categorized as balanced at 1.13:1. TKG of male and female mudskipper are I-IV with IGS values of 0-1.9% (males) and 0-4.7% (females). Fecundity values were categorized as medium to high with TKG III (4,088 ± 2,680 grains) and TKG IV (10,142 ± 2808 grains). Histology of TKG I (spermatogonium and primary spermatocytes), TKG II (primary and secondary spermatocytes), TKG III (secondary spermatocytes and spermatids), and TKG IV (spermatids and spermatozoa). Meanwhile, female octopus TKG I (primary oocytes), TKG II (secondary oocytes), TKG III (secondary oocytes and ootids), and TKG IV (ootids).